KELOMPOK USAHA BERSAMA (KUBE) DALAM RANGKA PEMBERDAYAAN EKONOMI MASYARAKAT MISKIN DI KABUPATEN PADANG LAWAS UTARA - Paisal Rahmat (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2021)
The economic empowerment of the poor in the Village is more needed than in the City, this shows that what is needed in rural areas must be more intensive. The importance of involving the community as a major supporter in development in Indonesia. This shows the change in the development paradigm to empowering the poor who directly manage their businesses. Along with the Joint Business Group (KUBE) meeting in Padang LawasUtara Regency. Through the Joint Business Group (KUBE) the community is empowered to support the economy channeled through the Social Service North Padang Lawas Regency, North Sumatra Province. The problem in this study was: How to empower the community economy through the Business Group (KUBE) in North Padang Lawas Regency. Regarding the objectives to be achieved in this study are: to study the Forms of the Implementation of Poor Economic Empowerment through Joint Business Groups (KUBE) in North Padang Lawas District, North Sumatra Province. This research includes qualitative research. The research conducted in this study is a field research with a descriptive method or approach. Descriptive research is a research method that addresses existing phenomena, which take place at this time or in the past. Descriptive research is intended to describe what situations or phenomena exist. The results of this study reveal that: The Economic Empowerment of the Poor through Joint Business Groups (KUBE) in the North Padang Lawas Regency is already underway with the concept of community economic empowerment in general, where members of the Joint Business Group (KUBE) are involved in various business activities. and the Office of Social Affairs accompanies, Monitoring and Evaluation in group business development. This success is measured by the principles of justice, equality, participation, appreciation for work ethic, please help (ta'awun)